Works of Russian scholars of the 15th to 20th centuries in the field of notation - Zakharina, Nina (Muzikološki zbornik, 2010)
The picture of the investigation of notation in Russia depends directly on history of musical writing in our country. The works on neumatic notation opened the tradition of musicology in Russia in the XV c. In the very beginning of the XIX c. neumes were examined as a historical phenomenon. The origin of Russian neumes became the central question in the XIX c., a central problem in the research of the XX c. was deciphering Russian neumes. In the very beginning of the XXI c. scholars pay attention to partly notated manuscripts, which reflect an oral tradition.
Keywords: nevme; srednjeveška muzikologija